ANALYSIS OF OPERATING REPORT FORM DESIGN IN SPECIAL KIDNEY RASYIDA MEDAN - Erlindai Purba (Akademi Perekam dan Informasi Kesehatan Imelda, 2020)
Abstract Form design is the activity of designing a form based on the transaction needs of service activities and the preparation or preparation of organizational reports. The surgery report is a surgical procedure for patients. To find out the design of the operation report form at the Rasyida Kidney Special Hospital in 2018. This type of research is a qualitative descriptive study. This research was conducted at the Rasyida Kidney Hospital in Medan, the population and sample used in this study were 1 Operation Report form used at the Rasyida Kidney Hospital in Medan, using the observation method. Based on the results of research on the design of the operation report form in Medan Rasyida Kidney Hospital, the anatomic aspects have not included a complete form heading and there is no clear introduction. From the physical aspect it is not appropriate because it still uses Kuwarto paper with a weight of 70 grams. While the content aspect is appropriate because it has been adapted to the 2008 Minister of Health Regulation. Based on the results of the study it can be suggested that the paper material should be replaced with A4 paper of at least 80 grams to reduce the risk of tearing and the need to add an explanation about filling out the operating report.